2016
DOI: 10.1093/jac/dkw053
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ceftolozane/tazobactam versus levofloxacin in the treatment of complicated urinary tract infections (cUTIs) caused by levofloxacin-resistant pathogens: results from the ASPECT-cUTI trial

Abstract: High urinary levels of levofloxacin did not reliably cure cUTIs. Seven day treatment with ceftolozane/tazobactam was more effective than high-dose levofloxacin treatment in patients with cUTI caused by levofloxacin-resistant bacteria, and it may be an alternative treatment in settings of increased fluoroquinolone resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 29 publications
1
14
0
1
Order By: Relevance
“…Herein, using ESBL-and non-ESBL-producing organisms, we assessed the translational value of this murine UTI model and humanized exposures for several frequently employed antimicrobial regimens for cUTI in humans. Levofloxacin displays poor clinical and microbiologic outcomes in the face of phenotypic resistance (9,10). Similar to these clinical outcomes, data derived in the current study show a lack of efficacy in an organism defined as nonsusceptible when exposed to a humanized regimen.…”
supporting
confidence: 67%
“…Herein, using ESBL-and non-ESBL-producing organisms, we assessed the translational value of this murine UTI model and humanized exposures for several frequently employed antimicrobial regimens for cUTI in humans. Levofloxacin displays poor clinical and microbiologic outcomes in the face of phenotypic resistance (9,10). Similar to these clinical outcomes, data derived in the current study show a lack of efficacy in an organism defined as nonsusceptible when exposed to a humanized regimen.…”
supporting
confidence: 67%
“…TOL/TAZ had a good safety profile and was superior to levofloxacin in terms of composite outcome (clinical cure and microbiological eradication) in 800 patients [24]. The difference was even greater in the subgroup of patients with levofloxacin-resistant bacteria [26]. In the CAZ/AVI trial, which enrolled a small sample (135 patients), microbiological and clinical responses were comparable in the active versus comparator arm, and CAZ/AVI was well tolerated [25].…”
Section: Role Of Tol/taz and Caz/avi In Therapymentioning
confidence: 99%
“…The composite cure rates for ceftolozane/tazobactam were superior in both the microbiological intention-to-treat population (76.9% versus 68.4%) and the per protocol population (83.3% versus 75.4%). A sub-group analysis that included baseline susceptibility testing showed that 2.7% of Gram-negative pathogens were resistant to ceftolozane/ tazobactam, whereas 26.7% of Gram-negative pathogens were resistant to levofloxacin and that among patients with levofloxacinresistant pathogens at baseline, the composite cure rate at the testof-cure visit was significantly higher in the ceftolozane/tazobactam group than the levofloxacin group [72]. In a pooled analysis of patients in the cIAI and cUTI trials where ESBL-producing Enterobacteriaceae were isolated showed that ceftolozane/tazobactam was highly effective with clinical cure in 97% of these patients [73].…”
Section: Clinical Studiesmentioning
confidence: 99%